Factually about the causes of addiction: A critical study (Academic Journal of Internal Affairs, 2019)
Unfortunatelly, most of people are convinced today, that the main causes of addiction are weakness of will and moral deficit. Even more serious problem is statements based on such moralizing and false information occur not just in coomonplace conversations. Some scientific authors and editors represent this exploded notion in their adacemic works as well. This study demonstrates the very complex bacground of causes of addiction for people that are primarly interested in law enforcement before psychology or health sciences. Causes of addictions are definitely not the weakness of will or moral deficit. The main causes of addiction are biological factors, social influences, psychological factors and other factors.
Keywords: addiction; biological factors; social influences; psychological factors